KEBIJAKAN HEDGING DENGAN INSTRUMEN DERIVATIF DALAM KAITAN DENGAN UNDERINVESTMENT PROBLEM DI INDONESIA - Repie, Renno Reynaldi; Sedana, Ida Bagus Panji (E-Jurnal Manajemen, 2015)
This study aims to testing the underinvestment hypothesis which predicts positive association between growth opportunities and hedging. This research population is miscellaneous industry sector companies in Indonesia Stock Exchange during 2010-2013. Purposive sampling was used for determining the sample. According to preset criteria, 23 sample and 92 firm-year observation is obtained. The hypothesis was tested using logistic regression analysis. The results shows that market to book value of equity (MBVE) has positive and significant impact on hedging activity, meanwhile the coefficient estimates of capital expenditure to book value of assets (CAPBVA) are positive but insignificant on hedging activity. Based on this results shows that the companies in miscellaneous industry sector motivation for use of derivatives instrument was not proven to mitigate the underinvestment problem.
Keywords: underinvestment, growth opportunities, hedging